Revisiting dithiadiaza macrocyclic chelators for copper-64 PET imaging. Issue 40 (24th September 2020) - Shuvaev, Sergey; Suturina, Elizaveta A.; Rotile, Nicholas J.; Astashkin, Andrei; Ziegler, Christopher J.; Ross, Alana W.; Walker, Tia L.; Caravan, Peter; Taschner, Ian S.
Abstract : Copper-64 complex with a new dithiadiaza macrocyclic chelator was evaluated as a PET tracer. Abstract : Synthesis and characterisation of a dithiadiaza chelator NSNS2A, as well as copper complexes thereof are reported in this paper. Solution structures of copper(i /ii ) complexes were calculated using density functional theory (DFT) and validated by both NMR and EPR spectroscopy. DFT calculations revealed a switch in the orientation of tetragonal distortion upon protonation, which might be responsible for poor stability of the Cu (II) NSNS2A complex in aqueous media, whilst the same switch in tetragonal distortion was experimentally observed by changing the solvent. The chelator was radiolabeled with 64 Cu and evaluated using PET/MRI in rats. Despite a favorable redox potential to stabilize the cuprous state in vivo, the 64 Cu (II) NSNS2A complex showed suboptimal stability compared to its tetraazamacrocyclic analogue, 64 Cu(TE2A), with a significant 64 Cu uptake in the liver.